Analisis Kemampuan Menulis Teks Persuasi Siswa Kelas IV Sekolah Dasar - Rere Oktavia Kuswoyo; Chandra Chandra; Salmaini Safitri Syam (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this study is to analyze the types of errors made by fourth-grade elementary school students in writing persuasive texts. This research uses a qualitative descriptive approach. Data were collected through document analysis of students' persuasive writing assignments. The study identified common errors related to structure, content coherence, language use, and spelling. The results showed that students frequently made mistakes in formulating persuasive arguments, organizing ideas logically, and applying appropriate linguistic features.